Frontlines of Fear and Healing: COVID-19 Community Quarantine Narratives of Filipino Community Health Workers - Mendres, Mark Yvanne Alcantara; Ancho, Inero Valbuena; Dy, Marison Felicidad Ranit; Vergara, Helga Payawal (Utan Kayu Publishing, 2025)
Although Filipino community health workers (CHWs) played a critical role during the COVID-19 community quarantine, many of them carried physical and psychological burdens. While various studies have indicated the negative experiences of healthcare workers during a health crisis, limited studies have explored the fear-related experiences of Filipino CHWs and their coping strategies to navigate these emotional challenges. Through a phenomenological study, this research gathered the narratives of seven female CHWs, including five Barangay Health Workers, one Municipal Midwife, and one Municipal Epidemiology and Surveillance Unit officer, assigned to three different barangays in Bay, Laguna. A semi-structured interview allowed the participants to share their fear and healing experiences during community quarantine. The results revealed that Filipino CHWs endured fear and anxiety about their health, as well as the well-being of their family members and the vulnerable population. Hence, they distanced themselves from their families by living in the workplace during the quarantine period. Despite these fear-related experiences, the families of the participants remained supportive, standing by their side even as they maintained distance. Coworkers also acted as a second family, offering emotional and practical support. These meaningful relationships helped them endure the challenges of the pandemic and continue their service to the community. These findings called on policymakers to empower the healthcare sector by not only prioritizing the physical well-being of CHWs but also their psychological welfare. Furthermore, support groups and health professionals may consider the role of family members in addressing the mental health challenges associated with the COVID-19 pandemic.